Single approach to double-channel core decompression and bone grafting with structural bone support for treating osteonecrosis of the femoral head in different stages - Ju’an Yue; Xiaozhong Guo; Randong Wang; Bing Li; Qiang Sun; Wangyan Liu; Jiao Chen; Yingnan Li (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background We created a novel method—single approach to double-channel core decompression and bone grafting with structural bone support (SDBS)—to treat early-stage osteonecrosis of the femoral head (ONFH) by improving the Phemister technique. This study aimed to evaluate the results of SDBS for early-stage ONFH. Methods Altogether, 53 patients (73 hips) were treated using SDBS during 2016–2018. Bilateral (20 patients) and unilateral (33 patients = 18 left hips, 15 right hips) ONFH was diagnosed. According to the Association Research Circulation Osseous classification stages, the femoral heads were staged as IIB (n = 15), IIC (n = 19), IIIA (n = 34), IIIB (n = 4), and IIIC (n = 1). The Harris hip score was used to evaluate the hips’ clinical function, computed tomography to evaluate subchondral fractures, and plain radiography to assess the extent of femoral head collapse. Results The average follow-up was 20.71 ± 6.65 months (6–36 months). At the patients’ last follow-up, 4 hips were found to require arthroplasty. Thus, the overall femoral head survival rate was 94.52% (69/73). Also, the overall Harris score (84.44 ± 14.57) was significantly higher than that preoperatively (77.67 ± 14.37) (P = 0.000). The combined excellent and good rate (76.71%) was significantly higher than that preoperatively (38.36%) (P = 0.000). Imaging showed that 16 femoral heads had some ONFH progression. The average length of stay was 6.15 ± 0.86 days. The average incision measured 2.69 ± 0.30 cm. Intraoperative blood loss was 61.20 ± 4.81 ml. There were no complications during or after the operation. Conclusion SDBS is an effective method for treating early-stage ONFH. It is a hip-preserving surgical approach to slow/prevent ONFH progression.